Ex vivo comparison of a novel tapered-sleeve and traditional full-limb transfixation pin cast for distal radial fracture stabilization in the horse - Elce, Y. A.; Southwood, L. L.; Nutt, J. N.; Nunamaker, D. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
Distal radial fractures in adult horses are examples of long-bone fractures that are not always amenable to internal fixation. These fractures are often open, contaminated, severely comminuted, and located adjacent to the antebrachiocarpal joint. There have been few studies to improve upon the methods of stabilization of this type of fracture. External coaptation incorporating transfixation pins is one method that has been used to stabilize distal radial fractures in horses (1–3). The purpose of this preliminary study was to compare the load to failure in simulated weight-bearing of a novel tapered-sleeve transfixation pin cast (TSTPC) (4) with the traditional transfixation pin cast (TPC) in an ex vivo distal radial fracture model. Ten adult equine cadaveric forelimbs were randomly placed into a TPC group (n=5) or a TSTPC group (n=5). An oblique distal radial osteotomy was created prior to application of fibreglass cast material. The limbs were loaded in a single cycle to failure in simulated weight-bearing using an axial load. The mean load to failure for the TSTPC group (35,814 N) was significantly greater than in the TPC group (22,344 N) (p=0.003). Tapered sleeves in conjunction with TPC warrant further investigation because they may prolong the life of the fixation, prevent or diminish fractures through the pin sites, and increase the load capacity of external coaptation used to stabilize equine fractures.
Keywords: Equine; fracture; transfixation pin cast; tapered-sleeve